Defect and interface engineering of MXene-tagged N, F-doped carbon-CoSe2 heterostructure for superior hydrogen evolution reactions and supercapacitors. (25th March 2023) - Ranjith, Kugalur Shanmugam; Lee, Seul-Yi; Ghoreishian, Seyed Majid; Chodankar, Nilesh R.; Rama Raju, Ganji Seeta; Patil, Swati J.; Huh, Yun Suk; Park, Soo-Jin; Han, Young-Kyu
Abstract: Defect and interface engineering on heterostructured electrode materials is an effective approach to improve the electrochemical performance of supercapacitors and water-splitting. Herein, we have prepared MXene nanosheets-tagged hetero atom-doped graphitic carbons wrapped CoSe2 (MXe-F, N- g CW-CoSe2 ) polyhedral heterostructure electrode material, and further investigated kinetic and thermodynamic factors that affect on defect and interface engineering to facilitate efficient electron and ionic path and promote the electrochemical active sites. The composites exhibit excellent hydrogen evolution reaction (HER) performances of the Tafel slope of 84.2 mV dec −1 and 94.5 mV dec −1 in 1 M KOH and 0.5 M H2 SO4, respectively. It also shows a high specific capacity of 403.4C g −1 at 1 A g −1 and the thus-assembled MXe-F, N- g CW-CoSe2 //AC hybrid supercapacitor revealed an energy density of 44.2 Wh kg −1 at a power density of 851.3 W kg −1 with superior stability of ∼94% after 10, 000 cycles. Graphical abstract: Image 1